CuO-TiO2-Chitosan-Berbamine Nanocomposites Induce Apoptosis through the Mitochondrial Pathway with the Expression of P53, BAX, and BCL-2 in the Human K562 Cancer Cell Line. (17th September 2022) - Elderdery, Abozer Y.; Alzahrani, Badr; Hamza, Siddiqa M. A; Mostafa-Hedeab, Gomaa; Mok, Pooi Ling; Subbiah, Suresh Kumar
Abstract : In this study, cells from human Chronic Myelogenous Leukemia (K562) were cultivated with CuO-TiO2 -Chitosan-Berbamine nanocomposites. We examined nanocomposites using XRD, DLS, FESEM, TEM, PL, EDAX, and FTIR spectroscopy, as well as MTT for cytotoxicity, and AO/EtBr for apoptotic morphology assessment. The rate of apoptosis and cell cycle arrests was determined using flow cytometry. Flow cytometry was also employed to identify pro- and antiapoptotic proteins such as Bcl2, Bad, Bax, P53, and Cyt C. The FTIR spectrum revealed that the CuO-TiO2 -Chitosan-Berbamine nanocomposites were electrostatically interlocked. The nanocomposites' XRD signals revealed a hexagonal shape. In the DLS spectrum, nanocomposites were found to have a hydrodynamic diameter. As a result of their cytotoxic action, nanocomposites displayed concentration-dependent cytotoxicity. The nanocomposites, like Doxorubicin, caused cell cycle phase arrest in K562 cells. After treatment with IC50 concentrations of CuO-TiO2 -Chitosan-Berbamine nanocomposites and Doxorubicin, a substantial percentage of cells were in G2/M stage arrest. Caspase-3, -7, -8, -9, Bax, Bad, Cyt C, and P53 expression were considerably enhanced in K562 cells, whereas Bcl2 expression was decreased, indicating that these cells may have therapeutic potential against human blood cancer/leukemia-derived disorders. As a result, the nanocomposites demonstrated outstanding anticancer potential against leukemic cells. CuO-TiO2 -Chitosan-Berbamine, according to our findings.